Change of plasma endothelin and cardiopulmonary function after exhausting - Shi, Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study is to explore the changes of plasma endothelin (ET) and cardiopulmonary function in endurance athletes after exhausting exercise. The correlation of cardio endocrine and cardiopulmonary function was also studied after exercise training.